Effect of Banana Fibers on the Compressive and Flexural Strength of Compressed Earth Blocks - Marwan Mostafa; Nasim Uddin (Buildings, 2015)
Sustainable development of the built environment in developing countries is a major challenge in the 21st century. The use of local materials in construction of buildings is one of the potential ways to support sustainable development in both urban and rural areas. Building with Compressed Earthen Blocks (CEBs) is becoming more popular due to their low cost and relative abundance of materials. The proposed Green-Compressed Earth Block (GCEB) consists of ordinary CEB ingredients plus Banana fibers, which will be the focus of this study. Banana fibers are widely available worldwide as agricultural waste from Banana cultivation. Banana fibers are environmentally friendly and present important attributes, such as low density, light weight, low cost, high tensile strength, as well as being water and fire resistant. This kind of waste has a greater chance of being utilized for different application in construction and building materials. This focused on the use of banana fiber and its effect on the compressive and flexural strength in CEB. The deflection at the mid-span of the blocks studied was calculated using the Linear Variable Differential Transformer (LVDT). The results of this study will highlight general trends in the strength properties of different soil mixes for CEBs. These efforts are necessary to ensure that GCEB technology becomes more widely accepted in the world of building materials and is considered a reliable option for providing low-cost housing.